Mineralogy, provenance, and diagenesis of a potassic basaltic sandstone on Mars: CheMin X‐ray diffraction of the Windjana sample (Kimberley area, Gale Crater). Issue 1 (29th January 2016) - Treiman, Allan H.; Bish, David L.; Vaniman, David T.; Chipera, Steve J.; Blake, David F.; Ming, Doug W.; Morris, Richard V.; Bristow, Thomas F.; Morrison, Shaunna M.; Baker, Michael B.; Rampe, Elizabeth B.; Downs, Robert T.; et al.
Abstract: The Windjana drill sample, a sandstone of the Dillinger member (Kimberley formation, Gale Crater, Mars), was analyzed by CheMin X‐ray diffraction (XRD) in the MSL Curiosity rover. From Rietveld refinements of its XRD pattern, Windjana contains the following: sanidine (21% weight, Or95 ); augite (20%); magnetite (12%); pigeonite; olivine; plagioclase; amorphous and smectitic material ( 25%); and percent levels of others including ilmenite, fluorapatite, and bassanite. From mass balance on the Alpha Proton X‐ray Spectrometer (APXS) chemical analysis, the amorphous material is Fe rich with nearly no other cations—like ferrihydrite. The Windjana sample shows little alteration and was likely cemented by its magnetite and ferrihydrite. From ChemCam Laser‐Induced Breakdown Spectrometer (LIBS) chemical analyses, Windjana is representative of the Dillinger and Mount Remarkable members of the Kimberley formation. LIBS data suggest that the Kimberley sediments include at least three chemical components. The most K‐rich targets have 5.6% K2 O, 1.8 times that of Windjana, implying a sediment component with >40% sanidine, e.g., a trachyte. A second component is rich in mafic minerals, with little feldspar (like a shergottite). A third component is richer in plagioclase and in Na2 O, and is likely to be basaltic. The K‐rich sediment component is consistent with APXS and ChemCam observations of K‐rich rocks elsewhere in Gale Crater. The source of this sediment component was likely volcanic. The presence of sediment from many igneous sources, in concert with Curiosity's identifications of other igneous materials (e.g., mugearite), implies that the northern rim of Gale Crater exposes a diverse igneous complex, at least as diverse as that found in similar‐age terranes on Earth. Key Points: First mineralogical analysis of sandstone on Mars Windjana sandstone very rich in sanidine, implying a trachyte source rock The source of Gale Crater sediments is an incredibly diverse igneous terrane